Fragmented Realities and Deconstructing Binary Oppositions in Mary Shelley's “Frankenstein” - Arain, Fakiha (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study explores how Mary Shelley’s Frankenstein deconstructs binary oppositions and delves into fragmented realities to interrogate traditional notions of identity, ethics, and power. Employing a post-structuralist lens, the research examines Shelley’s narrative techniques, which blur the boundaries between creator and creation, human and monster, and good and evil. Through fragmented perspectives, including layered narratives and shifting viewpoints, Shelley destabilizes conventional identities, prompting readers to confront moral complexities and question simplistic categorization. This analysis uncovers how the novel’s fragmented narrative structure challenges the stability of identity, raising ethical questions about societal rejection, scientific ambition, and the boundaries of human responsibility. By deconstructing binary oppositions and exploring the implications of fragmented realities, this study sheds light on Frankenstein’s enduring relevance in contemporary discussions on scientific ethics, identity formation, and social justice.